Rhodium(III)-Catalyzed ortho-C–H Alkylation of 2-Arylbenzothiazoles and 2-Arylthiazoles with Potassium Alkyltrifluoroborates - Ping, Yuanyuan; Chen, Zhaobin; Ding, Qiuping; Peng, Yiyuan (Synthesis, 2017)
A general and efficient Rh(III)-catalyzed ortho-C–H alkylation of 2-arylbenzothizazoles and 2-arylthiazoles with potassium alkyltrifluoroborates has been developed. The present method leads to the construction of a library of alkylated 2-arylbenzothiazoles and 2-arylthiazoles with yields up to 99%.
Keywords: alkylation; alkyltrifluoroborates; 2-arylbenzothiazoles; 2-arylthiazoles; transition metal